Cutinase-like biodegradable plastic-degrading enzymes from phylloplane yeasts have cutinase activity. Issue 8 (23rd June 2021) - Ueda, Hirokazu; Tabata, Jun; Seshime, Yasuyo; Masaki, Kazuo; Sameshima-Yamashita, Yuka; Kitamoto, Hiroko
ABSTRACT: Phylloplane yeast genera Pseudozyma and Cryptococcus secrete biodegradable plastic (BP)-degrading enzymes, termed cutinase-like enzymes (CLEs). Although CLEs contain highly conserved catalytic sites, the whole protein exhibits ≤30% amino acid sequence homology with cutinase. In this study, we analyzed whether CLEs exhibit cutinase activity. Seventeen Cryptococcus magnus strains, which degrade BP at 15 °C, were isolated from leaves and identified the DNA sequence of the CLE in one of the strains. Cutin was prepared from tomato leaves and treated with CLEs from 3 Cryptococcus species ( C. magnus, Cryptococcus flavus, and Cryptococcus laurentii ) and Pseudozyma antarctia (PaE). A typical cutin monomer, 10, 16-dihydroxyhexadecanoic acid, was detected in extracts of the reaction solution via gas chromatography–mass spectrometry, showing that cutin was indeed degraded by CLEs. In addition to the aforementioned monomer, separation analysis via thin-layer chromatography detected high-molecular-weight products resulting from the breakdown of cutin by PaE, indicating that PaE acts as an endo-type enzyme. Graphical Abstract: